PUBLIC-PRIVATE COLLABORATION STRATEGIES IN HANDLING MULTIDIMENSIONAL FINANCIAL CRISES - Jackson Yumame; Henderina Morin; Iyad Abdallah Al-Shreifeen (Adisam Publisher, 2025)
Multidimensional financial crises require coordinated and innovative responses from various stakeholders, especially the public and private sectors. This study aims to examine public-private collaboration strategies in handling multidimensional financial crises through a literature review of relevant literature, regulations, and case studies. The results of the study indicate that public-private collaboration can strengthen the effectiveness of crisis responses through various models, such as infrastructure partnerships, credit restructuring, financing innovations, and the development of cross-sector forums. Successful collaboration strategies are characterised by clear division of roles and risks, transparent governance, and adaptive policy support. However, challenges such as capacity constraints, differences in interests, and moral hazards remain major obstacles that need to be anticipated. This study emphasises the importance of strengthening regulatory frameworks, monitoring, and continuous evaluation so that public-private collaboration can become the main foundation in building national economic resilience amid increasingly complex crisis dynamics.